The Legitimacy of the Middle Ages : On the Unwritten History of Theory - Smith, D. Vance, 1963-; Cole, Andrew, 1968- (Book collections on Project MUSE., 2010)
Offers an assessment of the place of the Middle Ages in critical theory.